Nursing protocols to reduce urinary tract infection caused by indwelling catheters: an integrative review - Miranda, Maria Estela de Queiroz [UNESP]; Rosa, Marcelo Ricardo [UNESP]; Castro, Meire Cristina Novelli E. [UNESP]; Fontes, Cassiana Mendes Bertoncello [UNESP]; Bocchi, Silvia Cristina Mangini [UNESP] (FapUNIFESP (SciELO), 2023)
Objectives: to analyze the production of knowledge in research articles about the effectiveness of nursing protocols for reducing indwelling urinary catheter dwell time and catheter-associated urinary tract infection rate in hospitalized adult and older patients. Methods: an integrative review of three full articles, available in the MEDLINE Complete-EBSCO, Scopus and Web of Science databases, from 01/01/2015 to 04/26/2021. Results: the three protocols reduced infection rates, and from the review/synthesis of their knowledge, a level IV body of evidence emerged to compose the nursing care process aimed at reducing indwelling urinary catheter dwell time and catheter-associated urinary tract infection. Final Considerations: this process gathers scientific evidence to support the elaboration of nursing protocols and, consequently, the conduction of clinical trials on its effectiveness in reducing urinary tract infection by indwelling urinary catheter.
Protocolos de enfermería para reducir la infección del tracto urinario causada por catéteres permanentes: revisión integradora
Protocolos de enfermagem para redução de infecção urinária por cateteres de demora: revisão integrativa
Keywords: Catheter-Related Infections; Indwelling Catheters; Nurses; Protocols; Urinary Catheterization